Fodder bank: An option to sustain livestock production during natural calamities - Das, M M; Singh, K K; Kumar, Anil; Pathak, P K (Indian Farming, 2015)
During calamities when crop fails, livestock is the only sector which can sustain the livelihood of farmers. The feeding of livestock is important for the survival of the existing stock during calamities. It is therefore of parmount importance the fodder bank should be established in those zones which are affected by natural calamities to mitigate the shortage of feeds and fodder and to sustain the animal survivability and livestock productivity.